2011
DOI: 10.1002/apj.456
|View full text |Cite
|
Sign up to set email alerts
|

Start‐up transients in a pneumatic foam

Abstract: In the current work, transient features of initiation in a gas-liquid pneumatic foam are investigated by measuring the evolution of volumetric liquid fraction as a function of height within the column. The addition of wash water to a flotation froth is only effective when the foam liquid fraction has reached a steady state. This makes start-up transients in pneumatic foam worthy of study. For the conditions adopted in the experiments, an approximately steady state was achieved after typically 500s, but there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In fact, a study of start-up transients in a column carrying pneumatic foam has shown that the photographic method of obtaining bubble size must be deficient [13] because some measurements indicated that bubbles were becoming smaller with height, and this observation is unphysical. Optical tomographical methods [14,15] have been previously employed to resolve the three-dimensional structure (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a study of start-up transients in a column carrying pneumatic foam has shown that the photographic method of obtaining bubble size must be deficient [13] because some measurements indicated that bubbles were becoming smaller with height, and this observation is unphysical. Optical tomographical methods [14,15] have been previously employed to resolve the three-dimensional structure (i.e.…”
Section: Introductionmentioning
confidence: 99%